Preparation of Ethosome Gel with Total Flavonoids from Vernonia anthelmintica (L.) Willd. for the Treatment of Vitiligo - Dongmei Qin; Yongjie Cui; Mengyue Zheng; Zhiguo Yang; Xinbing Wang (Gels)
Vernonia anthelmintica (L.) Willd. is a traditional medicinal herb in Chinese medicine, extensively used by various ethnic groups due to the numerous advantages derived from its total flavonoids. These benefits encompass anti-inflammatory and antioxidant effects, and the promotion of melanin production, showcasing its significant efficacy in addressing vitiligo. To improve transdermal absorption and enhance the antioxidant effectiveness of the treatment, ethosome containing total flavonoids were prepared utilizing the ultrasound injection technique. The resulting ethosome was then carefully mixed with 0.7% Carbomer 934 gel in equal parts, yielding a gel concentration of 0.302 mg/g. This formulation produced small, consistent ethosome that exhibited high encapsulation efficiency and notable stability. In vitro analyses demonstrated sustained release characteristics of the gel and considerable therapeutic effectiveness against vitiligo resulting from hydroquinone exposure. Histological examinations performed through hematoxylin and eosin (H&E) staining of mouse skin revealed increased melanin production and increased activities of tyrosinase (TYR), cholinesterase (CHE), and mouse monoamine oxidase (MAO), while levels of superoxide dismutase (SOD) and malondialdehyde (MDA) were reduced. These findings underscore the promising effectiveness of this treatment strategy and validate the efficacy of the dosage form.